2019
DOI: 10.1109/access.2019.2953496
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach of Hybrid Trigonometric Bézier Curve to the Modeling of Symmetric Revolutionary Curves and Symmetric Rotation Surfaces

Abstract: The modeling of Bézier curves and surfaces with their shape parameters is the most popular area of research in computer aided geometric design/computer aided manufacturing (CAGD/CAM) due to their geometric characteristics. In this paper, we propose an important idea to tackle the problem in construction of some engineering symmetric revolutionary curves and symmetric rotation surfaces by using the generalized hybrid trigonometric Bézier (or GHT-Bézier, for short) curve. The shape of the curves and surfaces can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…two dimensional 3D three dimensional CAD computer-aided design NURBS non-uniform rational B-spline C 3 parametric continuity of degree three C 5 parametric continuity of degree five CPU central processing unit…”
Section: Dmentioning
confidence: 99%
See 1 more Smart Citation
“…two dimensional 3D three dimensional CAD computer-aided design NURBS non-uniform rational B-spline C 3 parametric continuity of degree three C 5 parametric continuity of degree five CPU central processing unit…”
Section: Dmentioning
confidence: 99%
“…In curve modeling, we deal with trigonometric Bézier-like [1][2][3][4][5], Q-Bézier [6], H-Bézier [7], Ball Bézier-like [8], S-λ Bézier-like [9], classical Bézier, B-spline, and NURBS curve, etc. Schoenberg introduced the trigonometric spline interpolation, spline interpolation of higher derivatives, interpolating spline as limit of polynomials, and Spline interpolation and best quadrature formulae in [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [36,37] proposed a method for constructing generalized developable Bézier and H-Bézier surfaces. Recently, Bibi et al [38] modeled symmetric revolutionary and rotational surfaces using a hybrid trigonometric Bézier surface that was later applied in engineering applications [39].…”
Section: Introductionmentioning
confidence: 99%
“…BiBi et al [17,18] suggested a new method for solving the problem of constructing symmetric curves and surfaces by using GHT-Bézier curves with four different shape parameters. e shape of curves can easily be modified by using different values of shape parameters.…”
Section: Introductionmentioning
confidence: 99%